1 Clarifying Educational Supervision in School Administration: A Case of Nigeria - Ijaiya, N.Y.S. (International Journal of Educational Management, 2022)
Internal school supervision remains an obscure, underrated and under-utilized tool of school administration particularly in Nigeria resulting in diminishing quality of education. While under-funding, poor infrastructure and weak teachers are being blamed for poor quality education, the role of school leadership receives little or no attention. This paper contends that Heads of schools as the school leader and supervisor has significant role to play in the quality equation but are hardly prepared for it due to ignorance and lack of training of career supervisors. Their role as educational supervisors therefore needs to be cleared. The paper discussed the nitty-gritty of school administration, breaking it down to administrative and instructional supervision and their constituents, the concept of educational supervision and processes, qualities expected from lesson presentation as well as the qualities of supervisors and supervisees. It highlighted several factors responsible for the cloudy nature of the administrative role of school Heads and consequences on the system. It was recommended, among others, that a programme at Postgraduate level be mounted in the Universities to train career supervisors in Nigeria and appointment of school leaders be based on such qualification and merit, not just as experienced teacher or on politics.